using the substitution method

5x +7y = -1
-6x + y = 20

2. What are you having trouble with, just eliminate one of the variables and solve for the other.

3. Originally Posted by mathdummy22
using the substitution method

5x +7y = -1
-6x + y = 20
Solve the second equation for y.

$\displaystyle y=6x+20$

Substitute 6x+20 for y in the first equation and solve for x.

Once you have x, you can use either equation to find y.

4. i get x = -139/47 and y= 106/47..... I have no clue what Im doing wrong

5. 5x +7y = -1
-6x + y = 20

y = 6x+20
7y = 42x +140
5x+42X+140 =-1 Here is where you screw up.
47x = -141
x = -3
y = 2 by substitution.

6. Solve the second equation for y.

$\displaystyle y=6x+20$

Substitute back into 1st equation:

$\displaystyle 5x+7(6x+20)=-1$

$\displaystyle 5x+42x+140=-1$

$\displaystyle 47x=-141$

$\displaystyle x=-3$

Now solve for y using $\displaystyle y=6x+20$

7. Originally Posted by terr13
5x+42X+140 =-1 Here is where you screw up.
When I screw something up, I always try to screw it back down.